Implementasi Data Mining Pola Penyakit Pasien Menerapkan Decision Tree J48 (Studi Kasus : RS.Estomihi) - Situmeang, Rohani (JURIKOM (Jurnal Riset Komputer), 2019)
Based on this the researcher is interested in A search pattern of large-scale data and that associate data with one another using Decision tree j48 algorithm. Thus the initial handling process of the patient will be less effective if in determining the type of patient's disease takes a long time . Apart from the problem, the results of analysis is also very necessary to avoid treatment errors, because if one in the treatment then it could be the illness suffered by patients can be more severe